The Concept of Love in the Poetry "Asyhadu An La Imraata Illa Anti" by Nizar Qabbani - Mahfudhoh, Vina Ulfa; Firdausi, M. Anwar (Diwan: Jurnal Bahasa dan Sastra Arab, 2023)
Love is one of the factors creating a poem. This research aims to provide an overview of the concept of love explained by Nizar Qabbani in the poem "Asyhadu an La Imraata Illa Anti" using Robert Sternberg's love triangle theory. The source of the data in this study was a poem by Nizar Qabbani entitled "Asyhadu an La Imraata Illa Anti". The data collection method in this study uses the method of listening to documentation techniques. The data analysis method in this study uses descriptive methods. The results of this research show that the elements contained in the poem "Asyhadu an La Imraata Illa Anti" are elements of intimacy, passion and commitment to form the concept of love. The concept of love that is formed from these three elements is true love, romantic love, and friendship love.